Combination of At-Sea Activity, Geolocation and Feather Stable Isotopes Documents Where and When Seabirds Molt - Cherel, Yves; Quillfeldt, Petra; Delord, Karine; Weimerskirch, Henri (Frontiers in Ecology and Evolution, 2016)
Key facets of the foraging ecology of seabirds during the inter-breeding period still remain poorly understood because of the difficulty of studying them at sea, including during the energy-demanding moulting stage. Here, the extent to which three sympatric petrels (Antarctic and thin-billed prions, and blue petrel) from the subantarctic Kerguelen Islands modify their foraging ecology during moult was investigated using a combination of complementary tools, namely miniaturized saltwater immersion geolocators (GLS) and the isotopic method. Firstly, moulting behaviour was first characterized in the blue petrel, a reference species that is known to renew its plumage in autumn. GLS and feather stable isotopes (13C as a proxy of the birds’ foraging habitat) indicated that the post-breeding moult of blue petrel occurred in Antarctic waters. Importantly, activity recorders showed that moult was marked by a strong peak in time spent daily sitting on water, which thereafter declined to lower values during the remaining winter months. Secondly, the peak in time spent sitting on water was used as a proxy to characterize the contrasted moult strategies of the two prion species. As blue petrels demonstrated, thin-billed prions moulted during the post-breeding period in cold Antarctic waters where they fed primarily on low trophic level prey, most likely Antarctic krill (15N as a proxy of the birds’ diet). By contrast, Antarctic prions presented an unexpected pre-breeding moult of longer duration that took place further north, in warm subtropical waters. Interestingly, the two Antarctic moulting species, the blue petrel and thin-billed prion, renewed their plumage at the same time and within the same oceanic zone that is likely to be a previously undescribed hot spot of seabird diversity during the Austral autumn. The study contributes to a growing body of evidence that closely-related species exhibit various foraging strategies allowing ecological segregation and sheds new light on the poorly known critical moulting stage of seabirds.